Mental health disorder in chronic liver disease: a questionnaire survey - Long, Jiang; Pei, Xiong; Jiang, Wei; Wang, Xiaoling; Wu, Dongbo; Tang, Xiangdong; Zhou, Taoyou (Frontiers in Psychiatry, 2024)
Background The mental health of patients with chronic liver disease (CLD) warrants greater attention and understanding, especially concerning its risk factors. Method Patients from our hospital’s hepatology clinic were consecutively enrolled and completed a questionnaire assessing anxiety, depression, and sleep quality using the GAD-7, PHQ-9, and PSQI scales, respectively. Reliability and validity were evaluated with Cronbach’s α and Kaiser-Meyer-Olkin (KMO). Continuous and categorical variables were analyzed using the Mann-Whitney U and Chi-square tests. Univariate and multivariate logistic regression were used to identify risk factors, while restricted cubic spline (RCS) were used to explored non-linear associations. Subgroup analyses were stratified by sex, age, and education. Result A total of 1030 questionnaires were collected, and after quality control, 1003 were included. 56.2% (564/1003), 53.2% (534/1003), and 67.4% (676/1003) individuals had anxiety, depression, and sleep disorders. Differences in age, gender, and education level were observed (P<0.05). Subgroup analysis showed similar demographic trends. Univariate and multivariate regression analysis found age negatively correlated with anxiety (OR=0.98, 95%CI=0.97-0.99, P=0.02) and depression (OR=0.98, 95%CI=0.96-0.99, P<0.001), but positively correlated with sleep disorders (OR=1.03, 95%CI= 1.01-1.05, P< 0.001); males are less prone to anxiety (OR=0.68, 95%CI=0.52-0.88, P=0.004) and sleep disorders (OR=0.72, 95%CI: 0.55-0.94, P=0.02); university degree is more susceptible to depression (OR=1.36, 95%CI=1.04-1.77, P=0.02) and anxiety (OR=1.45, 95%CI=1.11-1.89, P=0.007). RCS analysis suggested a linear relationship between the age and affective disorders among different population. Conclusion Young individuals, female, and those with higher education are more vulnerable to mental health, warranting increased attention.